Pheromone action regulates G-protein alpha-subunit myristoylation in the yeast Saccharomyces cerevisiae. - Dohlman, H G (1993)
Myristic acid (C14:0) is added to the N-terminal glycine residue of the alpha subunits of certain receptor-coupled guanine nucleotide-binding regulatory proteins (G proteins). The G alpha subunit (GPA1 gene product) coupled to yeast pheromone receptors exists as a pool of both myristoylated and unmyristolyated species. After treatment of MATa cells with alpha factor, the myristoylated form of Gpa1p increases dramatically, and the unmyristoylated form decreases concomitantly. This pheromone-stimulated shift depends on the function of STE2 (alpha-factor receptor), STE11 (a protein kinase in the response pathway), and NMT1 (myristoyl-CoA:protein N-myristoyltransferase) genes and uses the existing pool of fatty acids (is not blocked by cerulenin). Myristoylated Gpa1p persists long after pheromone is removed. Because myristoylation is essential for proper G alpha-G beta gamma association and receptor coupling, pheromone-dependent stimulation of Gpa1p myristoylation may be an important contributing factor in adaptation after signal transmission.